Raman spectroscopy as a tool for predicting the dimensionality and octahedra connectivity in lead iodide perovskites - Gjorgjevikj, K., Bukleski, M., Dimitrovska-Lazova, S., Aleksovska, S. (My University, 2023)
The interesting properties of the perovskite materials, especially the organic-inorganic ones are a consequence of their structural characteristics. In order to define the origin of these properties, a detailed structural characterization involving analysis with vibrational spectroscopy techniques has been undertaken. In this work, several inorganic and organic-inorganic lead iodide perovskites (RbPbI3, CsPbI3, CH3NH3PbI3, CH(NH2)2PbI3, C(NH2)3PbI3, (CH3)2NH2PbI3, (CH2)4NH2PbI3) were investigated by means of vibrational spectroscopy at room and low temperature and X-ray powder diffraction. Focusing on the Raman spectra, we followed the differences appearing in perovskites with different dimensionality. The bands that occur below 200 cm–1, their shape, relative position, intensity and shift can be related to the octahedral connectivity of the PbI6 anions, which, on the other hand, influence the dimensionality of the perovskites. Therefore, Raman spectroscopy can be used as a supporting technique for fast and reliable identification of octahedral connectivity.
Keywords: Lead iodide perovskites, Vibrational spectroscopy, X-ray powder diffraction (powder XRD/PXRD)